Searching for dark matter in the Sun using Hyper-Kamiokande. Issue 11 (4th November 2021) - Bell, Nicole F.; Dolan, Matthew J.; Robles, Sandra
Abstract: We study the ability of the Hyper-Kamiokande (HyperK) experiment, currently under construction, to constrain a neutrino signal produced via the annihilation of dark matter captured in the Sun. We simulate upward stopping and upward through-going muon events at HyperK, using Super-Kamiokande (SuperK) atmospheric neutrino results for validation, together with fully and partially contained events. Considering the annihilation of dark matter to various standard model final states, we determined the HyperK sensitivity to the dark matter spin-dependent scattering cross-section. We find that HyperK will improve upon current SuperK limits by a factor of 2–3, with a further improvement in sensitivity possible if systematic errors can be decreased relative to SuperK.